CAGE-miR-140-5p-Wnt1 Axis Regulates Autophagic Flux, Tumorigenic Potential of Mouse Colon Cancer Cells and Cellular Interactions Mediated by Exosomes - Yeon, Minjeong; Lee, Seungheon; Lee, Joo-Eun; Jung, Hyun Suk; Kim, Youngmi; Jeoung, Dooil (Frontiers in Oncology, 2019)
Although the cancer/testis antigen CAGE has been implicated in tumorigenesis, the molecular mechanism of CAGE-promoted tumorigenesis has not been extensively studied. CT26Flag-CAGE cells, CT26 (mouse colon cancer cells) cells stably expressing CAGE, were established for better understanding of CAGE-promoted tumorigenesis. Down-regulation of CAGE decreased autophagic flux in CT26Flag-CAGE cells. CAGE showed binding to Beclin1, a mediator of autophagy. CT26Flag-CAGE cells showed enhanced autophagosomes formation. CT26Flag-CAGE cells displayed greater tumor spheroid forming potential than did CT26 cells. MicroRNA array analysis revealed that CAGE decreased expression of various microRNAs including miR-140-5p in CT26. CAGE showed binding to the promoter sequences of miR-140-5p. MiR-140-5p inhibitor increased autophagic flux in CT26, and enhanced the tumorigenic potential of CT26. MiR-140-5p mimic decreased the tumorigenic potential of CT26Flag-CAGE cells, and autophagic flux in CT26Flag-CAGE cells. TargetScan analysis predicted wnt1 as a target of miR-140-5p. CT26Flag-CAGE cells showed higher expression of Wnt1 than did CT26. Down-regulation of Wnt1 decreased autophagic flux. Luciferase activity assays showed the direct regulation of wnt1 by miR-140-5p. The tumor tissue derived from CT26Flag-CAGE cells revealed higher expressions of hallmarks of activated mast cells and tumor-associated macrophages than the tumor tissue derived from CT26. Culture medium of CT26Flag-CAGE cells, increased autophagic flux in CT26, mast cells and macrophages. Culture medium of CT26Flag-CAGE cells, in a wnt1-dependent manner, increased CD163 and autophagic flux in CT26, mast cells and macrophages. Exosomes from CT26Flag-CAGE cells increased autophagc flux in CT26, mast cells and macrophages. Exosomes from CT26Flag-CAGE cells increased the tumorigenic potential of CT26. Wnt1 was shown to be within the exosomes. Recombinant wnt1 protein increased autophagic flux in CT26, mast cells, and macrophages. Recombinant wnt1 protein mediated interactions among CT26, mast cells, and macrophages. Our results show the novel roles of CAGE-miR-140-5p-wnt1 axis in autophagic flux and cellular interactions mediated by exosomes.